Investigation Of Boron Spin On Dopant On SOI Wafer - Bahaudin, Aishah Shamimi (Universiti Sains Malaysia, 2022)
In this research, works were focused on the doping technique of p-type SOI wafers by using thermal diffusion process. The aim of this research was to prepare doped of p-type SOI wafer by SOD with boron dopant. This method is used to provide an impurity source for SOI wafer. The dopant was first spread into the substrate via SOD and then diffused by a thermal diffusion process at 700˚C, 800˚C, 800˚C and 1000˚C. Various characterization instruments were used to investigate the properties of SOD technique on doping. Four-point probe was done to obtain the resistivity and sheet resistance of doped SOI wafer. The resistivity was decrease as well as sheet resistance with increasing the diffusion time and temperature. The dopant concentration was increased as the diffusion time and temperature increased. The surface roughness of doped SOI wafer for 120 minutes of diffusion were analyse using AFM. From the analysis, RMS values were obtained to describe the surface roughness after thermal diffusion. From result, the surface roughness around 30.0 nm to 80.0 nm were obtained with increasing diffusion temperature. However, at 900˚C, the RMS value was decrease due to etchant effect. To conclude, the selected thermal diffusion temperature is at 900˚C would lead to the best result SOD as it has high concentration, high carrier density, lower mobility and lowest surface roughness which the value of 7.17E+15cm−3, 8.506E+14 1/cm2, 4.885E+2 cm2/vs and 34.92nm respectively.